Epigenetic Changes in the Pathogenesis of Rheumatoid Arthritis - Nemtsova, Marina V.; Zaletaev, Dmitry V.; Bure, Irina V.; Mikhaylenko, Dmitry S.; Kuznetsova, Ekaterina B.; Alekseeva, Ekaterina A.; Beloukhova, Marina I.; Deviatkin, Andrei A.; Lukashev, Alexander N.; Zamyatnin, Andrey A. (Frontiers in Genetics, 2019)
Rheumatoid arthritis (RA) is a systemic autoimmune disease that affects about 1% of the world’s population. The etiology of RA remains unknown. It is considered to occur in the presence of genetic and environmental factors. An increasing body of evidence pinpoints that epigenetic modifications play an important role in the regulation of RA pathogenesis. Epigenetics causes heritable phenotype changes that are not determined by changes in the DNA sequence. The major epigenetic mechanisms include DNA methylation, histone proteins modifications and changes in gene expression caused by microRNAs and other noncoding RNAs. These modifications are reversible and could be modulated by diet, drugs and other environmental factors. Specific changes in DNA methylation, histone modifications and abnormal expression of noncoding RNAs associated with RA have already been identified. This review focuses on the role of these multiple epigenetic factors in the pathogenesis and progression of the disease, not only in synovial fibroblasts, immune cells, but also in the peripheral blood of patients with RA, which clearly shows their high diagnostic potential and promising targets for therapy in the future.